Costs and 30-day readmission after lower limb fractures from motorcycle crashes in Queensland, Australia: A linked data analysis. Issue 10 (October 2022) - Smith, Samuel; McCreanor, Victoria; Watt, Kerrianne; Hope, Matthew; Warren, Jacelle
Highlights: Lower limb fracture was the primary reason for hospital admission for over 3300 injured motorcyclists in Queensland between 2011 and 2017. The acute hospital treatment of lower limb fractures costs, on average, AU29, 044. Unplanned 30-day readmission occurred in 6.3% of the cohort and had an average cost of approximately AU11, 000. Readmissions were most commonly associated with continued fracture care, infection or post-operative complication. Abstract: Background: Lower limb trauma is the most common injury sustained in motorcycle crashes. There are limited data describing this cohort in Australia and limited international data establishing costs due to lower limb trauma following motorcycle crashes. Methods: This retrospective cohort study utilised administrative hospitalisation data from Queensland, Australia from 2011–2017. Eligible participants included those admitted with a principal diagnosis coded as lower extremity or pelvic fracture following a motorcycle crash (defined as the index admission). Multiply injured motorcyclists where the lower limb injury was not coded as the primary diagnosis ( i.e. principal diagnosis was rather coded as head injury, internal organ injures etc.) were not included in the study. Hospitalisation data were also linked to clinical costing data. Logistic regression was used to determine risk factors for 30-day readmission. Costing data were compared between those readmitted and those who weren't, using bootstrapped t -tests and ANVOA. Results: A total of 3342 patients met eligibility, with the most common lower limb fracture being tibia/fibula fractures (40.8%). 212 participants (6.3%) were readmitted within 30-days of discharge. The following were found to predict readmission: male sex (OR 1.84, 95% CI 1.01–1.94); chronic anaemia (OR 2.19, 95% CI 1.41–3.39); current/ex-smoker (OR 1.60, 95% CI 1.21–2.12); emergency admission (OR 2.77, 95% CI 1.35–5.70) and tibia/fibula fracture type (OR 1.46, 95% CI 1.10-1.94). The most common reasons for readmission were related to ongoing fracture care, infection or post-operative complications. The average hospitalisation cost for the index admission was AU29, 044 (95% CI 27, 235-30, 853) with significant differences seen between fracture types. The total hospitalisation cost of readmissions was almost AU2 million over the study period, with an average cost of 10, 977 (95% CI 9, 131- 13, 059). Conclusions: Unplanned readmissions occur in 6.3% of lower limb fractures sustained in motorcycle crashes. Independent predictors of readmission within 30 days of discharge included male sex, chronic anaemia, smoking status, fracture type and emergency admission. Index admission and readmission hospitalisation costs are substantial and should prompt health services to invest in ways to reduce readmission.